Education and gender: training social educators - Encarnación Bas-Peña; Victoria Pérez-; Montserrat Vargas Vergara (Sociedad Iberoamericana de Pedagogía Social, 2013)
Fromthe Universal Declaration of Human Rights international organizations have launched initiatives to achieve men and women equality and withstand all forms of discrimination and violence. This paper presents the research on gender training of students in Spanish universities that taught the Degree in Social Education. It was conducted in 36 universities (29 public and 7 private).We used a multi-method perspective.We performed a deep analysis of the degree programme through the teaching guides for all courses, in order to identify the presence of gender related areas in specific subjects and in those that include it transversely.We have also set up an on-line questionnaire for 4th year students (213 people), in order to have their opinion on the gender training received throughout their careers.We detected the weak presence, in the degree programmes, of specific subjects related to these topics. Most of the current focus is on gender equality / inequality, being residual the inclusion / exclusion and violence concepts. The subjects that transversely teach it are mostly mandatory and basic. The results extracted from the questionnaire include that students do received little training on these topics.While they give great importance to gender training. They show great unawareness about their right to receive such training and in addition be able to claim it. As well as not having knowledge of the Equality Plan in their university. A high percentage of respondents declared using sexist language, but it is still higher the percentage of students who said that teachers use it in their classes